2018
DOI: 10.1177/0963689718814766
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Roles of Urinary Trypsin Inhibitor in Brain Injury Following Fat Embolism Syndrome in a Rat Model

Abstract: Fat embolism syndrome (FES) is a common complication following long bone fracture; fat droplets are released into the blood circulation and form embolisms, mainly in lung and brain. However, the potential mechanisms involved remain to be clarified. In this study, the mechanism of brain injury following FES and the protective effects of urinary trypsin inhibitor (UTI)—a serine protease inhibitor—were investigated. Sixty male Sprague-Dawley rats were divided randomly into sham, FES and FES+UTI treatment groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…It has been reported that the TLR2/4-mediated NF-κB signaling pathway is an important regulatory mechanism in coronary microembolization-induced myocardial injury (22). In addition, a previous study has highlighted the crucial role of TLR4 in the regulation of fat embolism syndrome via the TLR-JNK signaling pathway (23).…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the TLR2/4-mediated NF-κB signaling pathway is an important regulatory mechanism in coronary microembolization-induced myocardial injury (22). In addition, a previous study has highlighted the crucial role of TLR4 in the regulation of fat embolism syndrome via the TLR-JNK signaling pathway (23).…”
Section: Discussionmentioning
confidence: 98%
“…UTI used as an injection is a glycoprotein originally extracted from fresh human urine, and it can inhibit the activities of various proteases. Like XBJ, UTI can inhibit the excessive release of in ammatory mediators, stabilize cell membrane structures, participate in in ammatory response regulation, and inhibit oxygen free radical and superoxide production [31][32][33][34][35]. It can also downregulate the expression of TGF-β1, TNF-α, and nuclear factor κB (NF-κB) [36] and reduce the levels of NSE and COX-2 [37], thereby protecting the organs of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Evans blue extravasation test was performed to examine the permeability of the blood-brain barrier as previously described [24]. Evans blue (2%, 4 mL/kg, Sigma, USA) was injected into the tail vein of the mice at 24 h after ICH.…”
Section: Assessment Of Blood-brain Barrier Permeabilitymentioning
confidence: 99%